Government spending and intergenerational income mobility: Evidence from China - Huang, Xiao; Huang, Shoujun; Shui, Ailun (Journal of economic behavior & organization, 2021)
By providing public service for equity and reducing the investment gap between rich and poor children, government spending plays a crucial role in intergenerational income mobility. With the China Health and Nutrition Survey data from 1989 to 2015, this paper assessed the relationship between government spending and intergenerational income mobility in China. First, we found that there was greater intergenerational mobility in high-spending provinces compared with low-spending provinces. Second, children with high per-capita government spending were more likely to experience upward mobility; this effect was twice as common in urban areas compared with rural areas. Third, government spending exerted influence on intergenerational income mobility through the mediation of education expansion. Higher government spending, which brought better quality in primary and secondary education, benefited poorer families more. In underdeveloped provinces, especially rural areas, government spending aimed at equal distribution of public services may provide more opportunities for the poor and lead to greater intergenerational income mobility in the future. Finally, the robustness checks that supported changing how income was measured or how government spending occurred did nothing to change our findings.